Incidence of cholelithiasis in patients diagnosed with obesity who underwent sleeve gastrectomy vs. laparoscopic Roux-en-Y gastric bypass. A retrospective study (Research, Society and Development, 2025)
Introduction: Cholelithiasis is a frequent metabolic complication after bariatric surgery, particularly in patients experiencing rapid weight loss and significant postoperative physiological changes. Objective: The objective of this study was to evaluate the relationship between the rate of weight loss and the development of cholelithiasis in patients undergoing bariatric surgery (gastric bypass or sleeve gastrectomy). Methods: An analytical, retrospective, and longitudinal observational study was conducted at a tertiary care hospital, including 401 adult patients who underwent bariatric surgery between January 2023 and June 2025. Clinical, anthropometric, and ultrasonographic data were analyzed at 3 and 6 months postoperatively. Weight loss rate was expressed in kg/month, and descriptive, bivariate, and adjusted logistic regression analyses were performed. Results: The incidence of cholelithiasis was similar between surgical techniques at 3 months but significantly higher in the gastric bypass group at 6 months (18.4% vs. 8.5%; p < 0.001). At 3 months, a higher rate of weight loss was independently associated with an increased risk of cholelithiasis, whereas this association was not observed at 6 months. No significant modifying effect of surgical technique was identified. Conclusion: Post-bariatric cholelithiasis was more frequent after gastric bypass; however, weight loss rate emerged as the main factor associated with gallstone formation, regardless of the surgical technique used.